Pengaruh Harga, Kualitas Produk, dan Pelayanan Terhadap Kepuasan Pelanggan Mie Gacoan di Palembang - Merisa Julianti (CV. Ulil Albab Corp, 2025)
This study aims to examine the significant impact of price on customer satisfaction at Mie Gacoan Palembang, investigate the influence of product quality on customer satisfaction, and explore the effect of service quality on customer satisfaction levels. The research employs a quantitative methodology. The study population encompasses all customers of Mie Gacoan Palembang, with a sample size of 100 respondents. Data collection was conducted through a research instrument that had been validated and tested for reliability. The data analysis method employed in this research was multiple regression analysis. The research findings, at a significance level of 5%, revealed that price exerts a positive influence on customer satisfaction, product quality provides a positive impact on job satisfaction, and service quality demonstrates a positive and significant effect on customer satisfaction.